2021
DOI: 10.1186/s40478-021-01126-5
|View full text |Cite
|
Sign up to set email alerts
|

Iron loading is a prominent feature of activated microglia in Alzheimer’s disease patients

Abstract: Brain iron accumulation has been found to accelerate disease progression in amyloid-β(Aβ) positive Alzheimer patients, though the mechanism is still unknown. Microglia have been identified as key players in the disease pathogenesis, and are highly reactive cells responding to aberrations such as increased iron levels. Therefore, using histological methods, multispectral immunofluorescence and an automated in-house developed microglia segmentation and analysis pipeline, we studied the occurrence of iron-accumul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 62 publications
5
87
2
Order By: Relevance
“…In Alzheimer's disease brains, the mRNA levels of TMEM119 were elevated, although no difference was observed in immunohistochemical analyses [28,45]. In contrast, Kenkhuis et al [47] demonstrated a microglial subset with an increased expression of the iron storage protein ferritin light chain (FTL) and IBA1, while exhibiting a decrease in TMEM119 and P2RY12 expression. This microglial subset presented a morphologically dystrophic phenotype.…”
Section: Tmem119mentioning
confidence: 95%
“…In Alzheimer's disease brains, the mRNA levels of TMEM119 were elevated, although no difference was observed in immunohistochemical analyses [28,45]. In contrast, Kenkhuis et al [47] demonstrated a microglial subset with an increased expression of the iron storage protein ferritin light chain (FTL) and IBA1, while exhibiting a decrease in TMEM119 and P2RY12 expression. This microglial subset presented a morphologically dystrophic phenotype.…”
Section: Tmem119mentioning
confidence: 95%
“…Magnetic resonance imaging has been less utilized than PET to assess gliosis due to its lack of cell specificity. Of note, it was recently suggested that iron associates with microglia in AD, especially in dystrophic microglia defined as senescent or dysfunctional ( Streit et al, 2009 ), and microglia primed to phagocytose Aβ ( Kenkhuis et al, 2021 ). MRI is very sensitive to iron ( Zeineh et al, 2015 ) and therefore might be used to find brain areas with microglial populations involved in AD.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…Through the production of these ROS, iron can induce severe brain damage [ 28 , 58 ]. Iron and ferritin are described to be associated with amyloid deposition and microglia [ 59 , 60 ]. Their levels are elevated in neuronal tissue and in the amyloid plaques [ 61 ].…”
Section: Products Of Oxidative Damage In Admentioning
confidence: 99%